Animal based diets and environment: Perspective from phosphorus flow quantifications of livestock and poultry raising in China. (15th August 2019) - Yuan, Zengwei; Ji, Jiaying; Sheng, Hu; Jiang, Songyan; Chen, Tianming; Liu, Xuewei; Liu, Xin; Zhuang, Yujie; Zhang, Ling
Abstract: Identifying the key nodes of the phosphorus flows in animal raising system is fundamental to improve P utilization efficiency and reduce the P contamination. This study established a phosphorus flow analysis model for livestock and poultry raising, depicted P flows for major livestock and poultry under two raising modes, and further analyzed their spatial and temporal distributions. We find that around 15% of P input was transferred into the products, and in P output around 40% lost into the environment in 2015. The P flows have been increasing since 2000, and the main contributor is pigs followed by beef cattle. It should be noticed that P loss from livestock and poultry raising is huge with extensive prospect of recycling in some central provinces of China, and western region where ecological environment is fragile, has a higher P loss rate which need to change the dietary preference and adjust raising structure. As for diets, pork and eggs are better choices than milk or other kinds of meat in terms of reducing the P load, when producing per unit protein or energy. This study contributes to the understanding of P management in husbandry industry, the quantification of environmental loads of animal-based food and the identification of the potential of reducing P loss to realize sustainable utilization of P. Graphical abstract: Image 1 Highlights: The P resources input had increased 51% from 2000 to 2015 in the system. P losses into environment had increased 72% from 1052 Gg in 2000 to 1805 Gg in 2015. Central provinces of China have extensive prospect of P waste utilization. PUE ranked as dairy cattle > layer poultry > pigs > broiler poultry > beef cattle > sheep. Pork and eggs are recommended animal-based food to reduce the P load.